The Effectiveness of the MABIT Program in Nurturing Religious Character in Children of Jorong Lurah Ampang - Sari, Novia Aspita; Maulana, Ilham; Ningsih, Silvi Rahayu; Haq, Afdhal Dinil; Firdaus, Firdaus; Ramyana, Fitriyani; Fauzi, Kasri Gunawan; Putri, Mentari Ghea Annisa; Irsyad, Mhd.; Hakim, Muhammad Abror; Rahmajanida, Reza; Aziza, Wardha; Salsabillah, Zikra (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2024)
Moral degradation among the younger generation has become an urgent issue in Jorong Lurah Ampang, Nagari Pasie Laweh, characterized by low religious understanding and inappropriate behavior. The Malam Bina Iman dan Taqwa (MABIT) program emerged as a solution to foster the religious character of children through a community-based approach. The primary objective of this initiative is to enhance participants' religiosity, worship discipline, and social skills. Activities are conducted using participatory methods, including lectures, hands-on practice, sermon training, Qur'an recitation, and recreational activities such as sports and discussions. The program results indicate significant improvements in prayer discipline, Qur'an reading and memorization skills, as well as behavioral changes among children, who have become more polite and responsible. The positive impact extends not only to the children but also to the community as a whole, fostering more harmonious social relationships and increasing parental involvement in children's religious education. With the support of the local community, the program has the potential to become a sustainable regular activity. The MABIT program demonstrates that a holistic approach rooted in religious values can be an effective model for nurturing the character of the younger generation.